E-Modul Berbasis Hypercontent: Upaya untuk Mengatasi Kesulitan Pembelajaran Sejarah di Masa Pandemi Covid-19 - Nuraeni Marta; Djunaidi Djunaidi; Corry Iriani (UIN Imam Bonjol Padang, 2022)
This article aims to review efforts to overcome the difficulties of learning history during the COVID-19 pandemic through teaching materials in the form of hyper-content-based e-modules. The Research qualitative methods, the main data is obtained from the results of in-depth interviews with key and core informants. Since mid-March 2020, face-to-face learning has been abolished and replaced by distance learning online. Teachers and students are forced to suddenly switch and adapt to using digital devices. This sudden change resulted in